Transdermal Delivery of Lidocaine-Loaded Elastic Nano-Liposomes with Microneedle Array Pretreatment - Yang Liu; Maosen Cheng; Junqi Zhao; Xiaoying Zhang; Zhen Huang; Yuhui Zang; Ying Ding; Junfeng Zhang; Zhi Ding (Biomedicines, 2021)
This study aimed to improve the transdermal delivery of lidocaine hydrochloride (LidH) using elastic nano-liposomes (ENLs) and microneedle (MN) array pretreatment. LidH-containing ENLs were prepared using soybean phosphatidylcholine and cholesterol, with Span 80 or Tween 80, using a reverse-phase evaporation method. The ENL particle size, stability, and encapsulation efficiency (EE) were characterized and optimized based on the component ratio, pH, and type of surfactant used. In vitro transdermal diffusion study was performed on MN-pretreated mouse skin using Franz diffusion cells. The anesthetic effects of LidH in various formulations after dermal application were evaluated in vivo in rats by measuring the tail withdrawal latency after photothermic stimulation. Stable LidH-loaded Tween 80 or Span 80 ENLs were obtained with particle sizes of 115.8 and 146.6 nm and EEs of 27% and 20%, respectively. The formulations did not exert any cytotoxicity in HaCaT cells. Tween 80 and Span 80 ENL formulations showed enhanced LidH delivery on pretreated mice skin in vitro and prolonged the anesthetic effect in vivo compared to that by LidH application alone. LidH-loaded ENLs applied to MN-pretreated skin can shorten the onset time and prolong the anesthetic effect safely, which merits their further optimization and practical application.